Understanding and Managing the Biotechnology Valley of Death. Issue 2 (February 2021) - Linton, Jonathan D.; Xu, Wei
Abstract : Biotechnology has a Valley of Death challenge. Arrhenius's model is used to consider this journey by visualizing the factors critical to identifying appropriate business models. Examples illustrate this interplay and the routes to industrial readiness. The insights provided are useful to research and development managers, policy makers, entrepreneurs, and biotechnologists.